Analysis of Transformer Turn Ratio Test Results on 60 MVA Power Transformer at Simpang Tiga Substation PT. PLN (Persero) ULTG Prabumulih - Fajri, Satria; Wibowo, Pristisal; Hamdani, Hamdani (Universitas Nusa Putra, 2025)
This research aims to compare the transformer turn ratio values obtained from testing with those calculated based on the transformer's nameplate data. The testing method used was the Transformer Turn Ratio (TTR) test, conducted with the Omicron CPC100 testing device. This test measures the ratio between the number of turns in the high-voltage and low-voltage windings at each tap of the transformer. The results of the comparison between the calculated values and the test results showed a variation in the range of 0.0045 to 0.0155. The deviation values from the test were found to be within acceptable limits, with the average deviation remaining below 0.5%. The deviation values ranged from -0.07% to -0.25%, all of which are well within the allowable limits according to the SK-DIR 0520 standard. Based on these findings, the 60 MVA three-phase transformer under study is deemed to be in good condition and suitable for energizing.